Analyzing the Impact of Collaborative Governance Models on Public Service Delivery - Indriati Amirullah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze the impact of collaborative governance models on public service delivery. Specifically, the study will examine how stakeholder-inclusive governance approaches can influence the effectiveness, efficiency, and quality of services provided by local governments. Collaborative governance involves the engagement of various stakeholders, including government agencies, non-governmental organizations, and the private sector, in the decision-making process to improve public service outcomes. This study posits that such inclusive approaches can enhance transparency, accountability, and responsiveness in public service delivery. Employing a qualitative case study methodology, data will be collected through interviews, observations, and document analysis. The selected case studies will encompass a diverse range of collaborative governance initiatives at the local level, providing a comprehensive understanding of different contexts and practices. By examining these cases, the research aims to identify the key factors that contribute to the success or failure of collaborative governance efforts. The analysis will focus on the impact of these initiatives on institutional capacity, such as the ability of local governments to mobilize resources, coordinate actions, and implement policies effectively. Furthermore, the study will evaluate the outcomes of these collaborative efforts in terms of service quality, accessibility, and user satisfaction. The findings are anticipated to offer valuable insights into the success factors and challenges associated with implementing collaborative governance models. These insights will be crucial for policymakers and practitioners seeking to enhance the performance of local governments in delivering improved public services. Ultimately, the research aims to contribute to the broader discourse on governance and public administration by highlighting the potential benefits and limitations of collaborative approaches in the public sector.